PERANAN PERBANKAN DALAM UPAYA MEMBANTU TUGAS PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN (PPATK) MENCEGAH PERANAN PERBANKAN DALAM UPAYA MEMBANTU TUGAS PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN (PPATK) MENCEGAH TERJADINYA PENCUCIAN UANG - Sang Ayu Made Ary Kusumawardhani (Fakultas Hukum Universitas Dwijendra, 2019)
The establishment of a special institution that handles money laundering in Indonesia, called the Financial Transaction Reports and Analysis Center (PPATK), as a central institution in the anti-money laundering system in Indonesia is regulated in Article 18 of the Republic of Indonesia Law No. 8 of 2010 concerning Prevention and Eradicating Money Laundering. The Financial Transaction Reports and Analysis Center (PPATK) is also an independent institution that has the duty and authority to prevent and eradicate money laundering, and to assist law enforcement relating to money laundering that is directly responsible to the President. The formulation of the problem in this research is: how is the financial service provider (Bank) in an effort to help the Financial Transaction Reports and Analysis Center (PPATK) prevent the occurrence of money laundering crimes and what obstacles and how the efforts of financial service providers in an effort to assist the Reporting and Analysis Center Financial Transactions (PPATK) prevent money laundering. The research method used in this study is normative legal research, namely by describing existing problems which are subsequently discussed and studied based on legal theories and then linked to the applicable laws and regulations in legal practice. The conclusions in this study are as follows: Financial service providers (Banks) in an effort to assist the Financial Transaction Reports and Analysis Center (PPATK) to prevent the occurrence of money laundering crimes has the main task of helping law enforcement agencies in preventing and overcoming money laundering crimes by providing intelligence information resulting from the analysis of reports submitted to the PPATK. Barriers to financial service providers in efforts to help the Financial Transaction Reports and Analysis Center (PPATK) prevent money laundering, among others: the presence of loopholes in financial service industry regulations, barriers from other laws and regulations, obstacles in international cooperation both by executive and judiciary and inadequate resources to prevent and find out about money laundering activities, for example the absence of a financial intelligent unit.Keywords: Banking, PPATK and Money Laundering